Rebozos de palabras : an Helena María Viramontes critical reader - Gutiérrez y Muhs, Gabriella (University of Arizona Press, 2013)
Helena María Viramontes is a professor, scholar-activist, and renowned author of works of fiction and nonfiction. Her work has been anthologized and is read widely in the United States and abroad. For many of her readings and speaking engagements she arrives wearing a rebozo, a shawl worn by Mexican and Chicana women living on both sides of the US-Mexico border. Once, when asked about her rebozo, Viramontes explained that the pre-Columbian icon is her "security blanket," which she embraces in order to find comfort. For her readers, her writing functions like a "rebozo de palabras," a shawl woven with words that nurture. As Gabriella Gutiérrez y Muhs points out in her insightful introduction, not only has Viramontes's work not yet received the broad critical engagement it richly deserves, but there remains a monumental gap in the interpretations of Chicana literature that reach mainstream audiences. Rebozos de Palabras addresses this void by focusing on how the Chicana image has evolved through Viramontes's body of work. With a foreword by Sonia Saldívar-Hull, this collection addresses Viramontes entire oeuvre through newly produced articles by major literary critics and emerging scholars who engage Viramontes's writing from multiple perspectives.--Amazon.com.